Pengaruh Good Corporate Governance Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sektor Industri Barang Konsusmsi Yang Terdaftar Di Bursa Efek Indonesia - Ana Dwi Agustin; Arik Susbiyani; Astrid Maharani (LPPM POLITEKNIK LP3I BANDUNG, 2023)
This study aims to examine how the influence of independent commissioners, managerial ownership, institutional ownership and audit committees on firm value in manufacturing companies in the consumer goods industry sector for the period 2019-2020 listed on the Indonesia Stock Exchange. The number of samples from this study was 214. The analytical tool used in this study was SPSS. The results of the analysis obtained in this study are Independent Commissioners have an effect on firm value, Managerial Ownership has no effect on firm value, Institutional Ownership has an effect on firm value and the Audit Committee has an effect on firm value.